The effect of combustion temperature to low-tar gas production using oxygen-enriched air - Viet, Dinh Quoc; Vinh, Nguyen Van; Cuong, Nguyen Tien; Luong, Nguyen Hoang; Son Tho, Van Dinh (Vietnam Journal of Chemistry, 2017)
Tar content in producer gas from biomass gasification is a serious problem for fuel gas utilization in downstream applications. This work presents the experimental studies of acacia woodchip gasification in a downdraft gasifier with two stages air supply. The effects of oxygen concentration in gasified agent on the temperature of gasifier, the syngas composition, the lower heating value and tar content in the producer gas are investigated. Results indicate that oxygen-enriched air rate not only favors to reduce tar component but also improves the heating value of the producer gas. When increasing oxygen concentration from 21 vol.% to 42 vol.% in the gasified agent, the tar content of the producer gas decreases from 67.4 mg/Nm3 to 30 mg/Nm3, hydrogen concentration increases from 7.28 to 13.15 vol.%, CO concentration increases from 19.65 vol.% to 26.52 vol.%, CH4 concentration increases from 1.4 to 3.3 vol.% and the low heating value increases from 4.45 MJ/m3 to 7.30 MJ/m3, respectively. On the other hand, the carbon conversion efficiency, gasification efficiency and gas yield of the gasifier are also presented in this approach. Keywords. Downdraft gasification, acacia woodchip, tar content, oxygen-enriched air.